Mathematical Equation for Precise Burr Hole Placement in Stereotactic Deep Brain Stimulation Lead Placement - Urakov, Timur M.; Jagid, Jonathan R. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Frame-based stereotactic lead placement for deep brain stimulation requires a carefully planned trajectory and approach. Point of entry at the cortex is usually selected to be over a gyrus avoiding veins. The angle of lead entry into the skull is different from the perpendicular direction of the burr drill. If the burr hole is not placed properly, the inner plate of the skull may be in the way of the lead, which creates a snowball effect of complications from trajectory readjustment to improperly fitting hardware. Using trigonometric principles, we elucidated a mathematical equation that predicts the precise position of the burr hole in order for the lead to enter exactly in the middle of the opening.
Keywords: deep brain stimulation; burr hole; stereotactic; equation